Enhanced astaxanthin production by oxidative stress using methyl viologen as a reactive oxygen species (ROS) reagent in green microalgae Coelastrum sp. - Ameerah Tharek; Shaza Eva Mohamad; Koji Iwamoto; Iwane Suzuki; Hirofumi Hara; Rozzeta Dolah; Shinji Yoshizaki; Haryati Jamaluddin; Madihah Md Salleh; Adibah Yahya (Indonesian Journal of Biotechnology, 2020)
Microalgae are known to be a potential resource of high-value metabolites that can be used in the growing field of biotechnology. These metabolites constitute valuable compounds with a wide range of applications that strongly enhance a bio-based economy. Among these metabolites, astaxanthin is considered the most important secondary metabolite, having superior antioxidant properties. For commercial feasibility, microalgae with enhanced astaxanthin production need to be developed. In this study, the tropical green microalgae strain, Coelastrum sp., isolated from the environment in Malaysia, was incubated with methyl viologen, a reactive oxygen species (ROS) reagent that generates superoxide anion radicals (O2-) as an enhancer to improve the accumulation of astaxanthin. The effect of different concentrations of methyl viologen on astaxanthin accumulation was investigated. The results suggested that the supplementation of methyl viologen at low concentration (0.001 mM) was successfully used as a ROS reagent in facilitating and thereby increasing the production of astaxanthin in Coelastrum sp. at a rate 1.3 times higher than in the control.